Role of the mutant spectrum in adaptation and replication of West Nile virus - Ciota, Alexander T. (2007)
West Nile virus (WNV) has successfully spread throughout the USA, Canada, Mexico, the Caribbean and parts of Central and South America since its 1999 introduction into North America. Despite infecting a broad range of both mosquito and avian species, the virus remains highly genetically conserved. This lack of evolutionary change over space and time is common with many arboviruses and is frequently attributed to the adaptive constraints resulting from the virus cycling between vertebrate hosts and invertebrate vectors. WNV, like most RNA viruses studied thus far, has been shown in nature to exist as a highly genetically diverse population of genotypes. Few studies have directly evaluated the role of these mutant spectra in viral fitness and adaptation. Using clonal analysis and reverse genetics experiments, this study evaluated genotype diversity and the importance of consensus change in producing the adaptive phenotype of WNV following sequential mosquito cell passage. The results indicated that increases in the replicative ability of WNV in mosquito cells correlate with increases in the size of the mutant spectrum, and that consensus change is not solely responsible for alterations in viral fitness and adaptation of WNV. These data provide evidence of the importance of quasispecies dynamics in the adaptation of a flavivirus to new and changing environments and hosts, with little evidence of significant genetic change.